trategy, diplomacy, humanity : life and work of Sahabzada Yaqub-Khan - Sahabzada Yaqub Khan (Islamabad Intercultural Forum Takshila Research University, 2005)
Lectures of an ex-Foreign Minister of Pakistan; includes his brief life sketch.
Keywords: Foreign relations. -- Pakistan